VD_FINDINFO Décision / 2013 / 199 vom 24. November 2011 - VD Tribunal cantonal (2011)
DÉTENTION PRÉVENTIVE, RISQUE DE RÉCIDIVE, PROLONGATION, PROPORTIONNALITÉ | 221 al. 1 let. c CPP (CH), 221 CPP (CH), 227 CPP (CH), 393 al. 1 let. c CPP (CH)